A typology of small-scale multilingualism. (August 2021) - Pakendorf, Brigitte; Dobrushina, Nina; Khanina, Olesya
Aims: The paper aims at providing an exhaustive overview of studies of small-scale multilingualism, a type of language ecology typical of—but not exclusive to—indigenous communities with small numbers of speakers. We identify the similarities and differences among situations of such multilingualism, which lay the foundations for a future typology of this kind of language ecology. Approach and data: We outline the importance of language ideologies for multilingualism in small-scale societies, highlight the sources of this type of language ecology, with a special focus on the impact of marriage patterns, discuss to what extent situations of small-scale multilingualism are truly egalitarian and symmetric, and survey the different methods used in the study of this domain. In order to do so, we survey studies devoted to multilingualism in indigenous communities of all continents: the New World (especially South America), Australia, Melanesia, Africa, Europe and Asia. Conclusions: The multilingual ecologies of the pre- and postcolonial world are extremely diverse, with many factors playing a role in their constitution. They are also highly endangered, and thus their study is of the utmost urgency. Originality: The domain of small-scale multilingualism is still novel for sociolinguistics and linguistic anthropology. Although the researchers working with indigenous groups have been describing the peculiarities of multilingual repertoires, language acquisition and language attitudes in various parts of the world, the domain lacks the kind of comparison and generalizations that we provide here. Significance: The increased interest in small-scale multilingualism has been boosted by the realization of its significance for reconstructing the social conditions that favoured linguistic diversity in the precolonial world. Furthermore, insights into this type of multilingualism—which differs considerably from the better-studied situations of bi- and multilingualism in urban contexts and large nation states—are of prime importance for a better understanding of the human language faculty.